Chemical Profile and Promising Applications of Cucurbita pepo L. Flowers - Ritamaria Di Lorenzo; Luigi Castaldo; Raffaele Sessa; Lucia Ricci; Eleonora Vardaro; Luana Izzo; Michela Grosso; Alberto Ritieni; Sonia Laneri (Antioxidants, 2024)
Although edible flowers have been historically principally used due to their visual appeal and smell, the world is discovering their value as innovative and natural sources of bioactive compounds. Cucurbita pepo L. (CpL), a plant from the Cucurbitaceae family, is widely cultivated for its edible fruits and flowers, which are rich in polyphenols and carotenoids—compounds known for their potent antioxidant and anti-inflammatory properties. Despite their potential, the use of CpL flowers for skin-related applications remains underexplored. This study aimed to comprehensively analyze CpL flower extract (CpLfe), focusing on its polyphenolic and carotenoid content using, for the first time, advanced UHPLC-Q-Orbitrap HRMS and HPLC-DAD analysis. CpLfe highlighted remarkable antioxidant activity according to the DPPH, ABTS, and FRAP tests. CpLfe showed significantly reduced intracellular ROS in HaCaT (23%, p < 0.05) and protected against UVB-induced damage by lowering MMP-1 expression. CpLfe also upregulated genes crucial for skin hydration (AQP3) and barrier function (CerS2, CerS4, and CerS6). A placebo-controlled, randomized clinical trial further validated CpLfe efficacy, demonstrating marked improvements in moisture retention, wrinkle reduction, and collagen production in women aged 35–55. These findings suggested that CpL flowers could be a source of bioactive compounds recovered from edible flowers able to improve the major skin aging and photoaging features.